The EU and the Political Economy of Transatlantic Relations - Laursen, Finn; Laursen, Finn (Peter Lang, 2013)
Transatlantic economic relations remain extremely important for the European Union as well as for other countries in the world. When it comes to trade and foreign direct investment, the EU and the United States remain arguably the world$1 (Bs most powerful actors, despite the financial crisis which started in the United States in 2007 and subsequently spread to Europe and to the Eurozone in particular. This crisis has created great economic strain on both Europe and North America, with politicians trying to muddle through and disagreeing on which strategy to adopt. The dominance of the Atlantic countries in the global political economy is now challenged by new emerging powers, including the so-called BRICS (Brazil, Russia, India, China and South Africa). These countries have succeeded in keeping much higher growth rates than Europe and North America, although they too are now affected by the global economic crisis. This book is focused on these issues as well as other issues in transatlantic relations, including competition and environment policy. Given the complex interdependence of transatlantic countries they need to work together to solve the issues that divide them.s